The intestinal microbiota determines the colitis‐inducing potential of T‐bet‐deficient Th cells in mice. Issue 1 (29th September 2017) - Zimmermann, Jakob; Durek, Pawel; Kühl, Anja A.; Schattenberg, Florian; Maschmeyer, Patrick; Siracusa, Francesco; Lehmann, Katrin; Westendorf, Kerstin; Weber, Melanie; Riedel, René; Müller, Susann; Radbruch, Andreas; et al.
Abstract: Conflicting evidence has been provided as to whether induction of intestinal inflammation by adoptive transfer of naïve T cells into Rag −/− mice requires expression of the transcription factor T‑bet by the T cells. Here, we formally show that the intestinal microbiota composition of the Rag −/− recipient determines whether or not T‐bet‐deficient Th cells can induce colitis and we have resolved the differences of the two microbiomes, permissive or non‐permissive to T‐bet‐independent colitis. Our data highlight the dominance of the microbiota over particular T cell differentiation programs in the pathogenesis of chronic intestinal inflammation. Abstract : Whether colitis induction by CD4 + T cells adoptively transferred into Rag −/− recipients requires their expression of the Th1‐lineage determining transcription factor T‐bet has been an ongoing debate. Here, we demonstrate that the recipient's intestinal microbiota composition determines whether or not T‐bet‐deficient Th cells can induce colitis.